Pengaruh Dana Transfer Terhadap Pertumbuhan Ekonomi (Studi Wilayah Sulawesi) - Anggun Geovanny Rahman; Sri Indriyani S Dai; Ivan Rahmat Santoso (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
Transfer funds from the central government to regional governments have an important role as the main fund in efforts to support regional expenditure financing, but Sulawesi's current economic growth has not shown maximum results, for this reason an investigative study of the effect of transfer funds on economic growth is crucial. This study aims to determine the effect of transfer funds (Profit Sharing Funds, General Allocation Funds, and Special Allocation Funds) on Sulawesi's economic growth. The data used is sourced from the Central Statistics Agency and the Ministry of Finance of the Republic of Indonesia. The method used is quantitative with panel data analysis. The results of this study indicate that the Profit-Sharing Fund variable has a significant negative effect on Sulawesi's economic growth, meaning that the Profit-Sharing Fund can significantly reduce the percentage of economic growth. The General Allocation Fund variable has a positive and significant impact on Sulawesi's economic growth, meaning that the General Allocation Fund can significantly increase the percentage of economic growth. The Special Allocation Fund variable has a significant negative impact on Sulawesi's economic growth, meaning that the Special Allocation Fund can significantly reduce the percentage of economic growth. The variables of Revenue Sharing Funds, General Allocation Funds, and Special Allocation Funds have an influence of 72 percent on Sulawesi's economic growth.